2016
DOI: 10.1016/j.ajpath.2016.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of CSE1L Gene in Colorectal Cancer Reduces Tumorigenesis in Vitro

Abstract: Human cellular apoptosis susceptibility (chromosomal segregation 1-like, CSE1L) gene plays a role in nuclear-to-cytoplasm transport and chromosome segregation during mitosis, cellular proliferation, and apoptosis. CSE1L is involved in colon carcinogenesis. CSE1L gene expression was assessed with three data sets using Affymetrix U133 + gene chips on normal human colonic mucosa (NR), adenomas (ADs), and colorectal carcinoma (CRC). CSE1L protein expression in CRC, AD, and NR from the same patients was measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 26 publications
(32 reference statements)
8
33
0
Order By: Relevance
“…Previous studies have found that CSE1L knockdown resulted in decreased cell proliferation, a reduction in colony formation in soft agar, and induction of apoptosis in colorectal cancer30. Yuksel et al 31.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that CSE1L knockdown resulted in decreased cell proliferation, a reduction in colony formation in soft agar, and induction of apoptosis in colorectal cancer30. Yuksel et al 31.…”
Section: Discussionmentioning
confidence: 99%
“…44 Pimiento reported that CSE1L knockdown inhibited cell proliferation and induced apoptosis in CRC cells. 45 Li found that CSE1L acted as an oncogene in gastric cancer (GC), and knockdown of CSE1L suppressed GC cell proliferation and metastasis via inhibition of glycoprotein nonmetastatic melanoma protein B (GPNMB) expression. 46 In this study, analysis of GEO datasets (GSE110224 and GSE37364) and IHC analysis showed that CSE1L was upregulated in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Also, CSE1L expression was increased in ovarian cancer, and the depletion of CSE1L impaired invasion and metastasis of ovarian cancer cells [ 32 ]. Moreover, as mentioned above, CSE1L was reported to be closely linked with the occurrence and progression CRC [ 14 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…CSE1L, highly expressed in various cancer types, plays important roles in apoptosis, cell survival, chromosome assembly, nucleocytoplasmic transport, microvesicle formation, and cancer metastasis [ 12 , 13 ]. In CRC, CSE1L expression was upregulated and CSE1L knockdown suppressed cell proliferation, metastasis, and induced apoptosis [ 14 16 ]. However, whether the effect of CSE1L on CRC pathogenesis was mediated by BANCR is still obscure.…”
Section: Introductionmentioning
confidence: 99%